Daily vision testing can expose the prodromal phase of migraine. (August 2018) - McKendrick, Allison M; Chan, Yu Man; Vingrys, Algis J; Turpin, Andrew; Badcock, David R
Background: Several visual tasks have been proposed as indirect assays of the balance between cortical inhibition and excitation in migraine. This study aimed to determine whether daily measurement of performance on such tasks can reveal perceptual changes in the build up to migraine events. Methods: Visual performance was measured daily at home in 16 non-headache controls and 18 individuals with migraine using a testing protocol on a portable tablet device. Observers performed two tasks: luminance increment detection in spatial luminance noise and centre surround contrast suppression. Results: Luminance thresholds were reduced in migraine compared to control groups ( p < 0.05), but thresholds did not alter across the migraine cycle; while headache-free, centre-surround contrast suppression was stronger for the migraine group relative to controls ( p < 0.05). Surround suppression weakened at around 48 hours prior to a migraine attack and strengthened to approach their headache-free levels by 24 hours post-migraine (main effect of timing, p < 0.05). Conclusions: Daily portable testing of vision enabled insight into perceptual performance in the lead up to migraine events, a time point that is typically difficult to capture experimentally. Perceptual surround suppression of contrast fluctuates during the migraine cycle, supporting the utility of this measure as an indirect, non-invasive assay of the balance between cortical inhibition and excitation.